WHAT DOES THE GUSTATORY PREFERENCES DEVELOPMENT IN INFANTS DEPEND ON? - I. N. Zakharova; Yu. A. Dmitrieva; E. А. Gordeeva ("Paediatrician" Publishers LLC, 2012)
Intensive development of the molecular biology, genetically engineered methods of examination and decoding of human genome rendered significant assistance to discoveries in the field of gustatory preferences and food behavior formation study in children. It was proved that gustatory preferences in children and, further, in adults are influenced by numerous factors. The main of such factors are genetic ones; peculiarities of pregnant woman and child nutrition; national food traditions. The afore-mentioned factors and possible ways of influence on them are considered in this article, which contributes to development of appropriate food behavior, playing a significant role in the formation of children' and adults' health.